Prohydrojasmonate–silicon synergy enhances cadmium detoxification and stress tolerance in rice, Oryza sativa L - AL-Amri, Salem M. (Frontiers in Plant Science, 2026)
Cadmium (Cd) contamination severely threaten rice productivity and food security, yet effective and sustainable detoxification strategies remain limited. This study investigates whether combined application of prohydrojasmonate (PDJ) and silicon (Si) can synergistically enhance Cd detoxification in rice. Rice seedlings exposed to Cd stress were treated with PDJ, Si or their combination and evaluated through integrated physiological, biochemical and molecular analyses including metal accumulation, photosynthetic performance, oxidative status, hormonal regulation and gene expression. Compared to individual treatments, PDJ-Si co-treatment significantly reduced Cd translocation to aerial tissues, with maximum root retention restored essential leaf elements (Fe, K, Mn) and enhanced photosynthetic efficiency. While PDJ and Si individually enhanced membrane stability, reduced lipid peroxidation and improved osmotic balance their combined application produced the most pronounced effects. Phytohormone profiling revealed coordinated activation of salicylic acid (SA) and jasmonic acid (JA) pathways with balanced abscisic acid (ABA) modulation. Furthermore, both individual and combine application caused differential expression of genes related to detoxification (OsABCC1, OsGSTU5, OsPCS1), metal transporters (OsHMA2, OsLCT1) and hormone biosynthesis (OsABA2, OsEDS1, OsAOS2). Collectively, these findings demonstrate that PDJ and Si application enhance Cd detoxification and stress tolerance in rice providing a promising approach for sustainable rice cultivation in Cd-contaminated soils.